POLITICAL SCIENCE AND SOCIOLOGY ON THE ROLE OF RELIGION IN THE AXIOLOGICAL AND MEANINGFUL SPACE OF KAZAKHSTAN SOCIETY - AMREBAEV, Aydar; BIZHANOV, Akhan; BUROVA, Elena (CENTRAL ASIA AND THE CAUCASUS, 2018)
The article is based on the latest sociological data and deals with the problem of axiological comprehension of the phenomenon of religiosity in Kazakhstan as part of a political science discourse. The authors have traced the evolution of the content and volumes of religiosity in Kazakhstan. They studied varied meaningful contents and the way they affect political decision-making in the sphere of spiritual development of society in the conditions of social, economic, and political transformations in Kazakhstan. They have assessed the importance of global trends of civilizational development in the time of international turbulence and their importance for socialization at the individual and collective levels. Interpretation of sociological data by political science identifies constructive and destructive roles of religion in the public consciousness of Kazakhstan citizens. The authors have studied the correlation between religiosity, quasi-religiosity, and secularity in the makeup of Kazakhstan society as we know it today. They have classified the trends obvious in the development of religiosity in Kazakhstan and addressed the problem of an adequate state policy in the religious sphere. The attitude of the Kazakhstan citizens to religious radicalization and the ways and means of its suppression, as well as the issue of applied importance, have been discussed. On the whole, the present article is a comprehensive discussion in terms of sociology and political science of the problem of great social importance for Kazakhstan and its Central Asian neighbors coping with more or less similar problems of interaction between the state and religion.